Anti-ErbB2 immunotherapeutics: struggling to make better antibodies for cancer therapy - Rita De Santis (Taylor & Francis Group, 2020)
Over the past 3 decades, monoclonal antibodies and their related derivatives, including recently approved antibody-drug conjugates, conquered a central role in cancer therapy because of their contribution to improve survival, time to progression and quality of life of patients compared to chemotherapy protocols. This review summarizes information on approved original and biosimilar products, as well as investigational antibody-based therapeutics, targeting ErbB2. This target has been selected as a paradigmatic example because of its relevant role in sustaining the malignancy of major cancer diseases including, breast, gastric and other chemotherapy-resistant solid tumors. This work analyzes the drivers affecting research and development of next-generation anti-ErbB2 immunotherapeutics, taking into account unmet medical needs and pharmacoeconomic issues related to sustainability. The analysis may help with the design of future research and development strategies.